2016
DOI: 10.1002/jemt.22740
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of hydrogels and decellularized tissue sections used in mechanobiology studies probed by atomic force microscopy

Abstract: The increasing recognition that tissue elasticity is an important regulator of cell behavior in normal and pathologic conditions such as fibrosis and cancer has driven the development of cell culture substrata with tunable elasticity. Such development has urged the need to quantify the elastic properties of these cell culture substrata particularly at the nanometer scale, since this is the relevant length scale involved in cell-extracellular matrix (ECM) mechanical interactions. To address this need, we have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 72 publications
(183 reference statements)
1
22
0
Order By: Relevance
“…It is worth noting that the stiffness measured in the reseeded decellularized matrices (mean 40-60 kPa) was higher than the values measured in native human lung parenchymal tissue (1.34±0.36 kPa; Liu et al, 2010 ) and IPF tissue (16.52±2.25 kPa; Booth et al, 2012 ). It has been reported in the literature that the decellularization method affects the stiffness of acellular tissue ( Melo et al, 2014 ) and, more generally, that decellularized tissue is stiffer than normal lung tissue ( Giménez et al, 2017 ), although the origins of these differences in decellularized versus normal tissue stiffness remain poorly understood. The reseeded decellularized matrices did not form alveolar structures in the time span of this study and were densely packed ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the stiffness measured in the reseeded decellularized matrices (mean 40-60 kPa) was higher than the values measured in native human lung parenchymal tissue (1.34±0.36 kPa; Liu et al, 2010 ) and IPF tissue (16.52±2.25 kPa; Booth et al, 2012 ). It has been reported in the literature that the decellularization method affects the stiffness of acellular tissue ( Melo et al, 2014 ) and, more generally, that decellularized tissue is stiffer than normal lung tissue ( Giménez et al, 2017 ), although the origins of these differences in decellularized versus normal tissue stiffness remain poorly understood. The reseeded decellularized matrices did not form alveolar structures in the time span of this study and were densely packed ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To culture fibroblasts in conditions that mimic the fibrotic mechanical microenvironment, we adapted two independent and complementary assays based on collagen-rich hydrogels with tunable elasticity as outlined in Figure 1 . Both assays have been widely used in previous mechanobiology studies [ 27 , 28 ]. The floating gel assay is based on culturing fibroblasts embedded in three-dimensional (3D) collagen-I gels that remain either attached to their container or floating, thereby providing high or low mechanical resistance, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work by this group Melo et al (2014b) demonstrated that the specific decellularization process affects the elastic modulus tissues, thus it is important to recognize that the additional variable of tissue preparation (frozen intact tissue versus decellularized) is not identical between the two studies and may also account for some of the observed differences. In support of this concept, it is notable that the mechanical properties of acellular ECM tissues are stiffer than normal lung tissue (Gimenez et al, 2017; Ott et al, 2010), though the explanation for this effect remains to be determined. In contrast to these comparable results with sharp tips, Meng et al (2015) reported similar elastic modulus values to those of Liu et al (2016) and our current results using larger spherical tips, but did so with the use of a sharp pyramidal tip (40 nm radius) and relatively thick tissue section.…”
Section: Discussionmentioning
confidence: 98%